Uncovering Infant Group B Streptococcal (GBS) Disease Clusters in the United Kingdom and Ireland Through Genomic Analysis: A Population-based Epidemiological Study. (7th August 2020) - Collin, Simon M; Groves, Natalie; O'Sullivan, Catherine; Jauneikaite, Elita; Patel, Darshana; Cunney, Robert; Meehan, Mary; Reynolds, Arlene; Smith, Andrew; Lindsay, Diane; Doherty, Lorraine; Davies, Eleri; et al.
Abstract: Background: The true frequency of hospital outbreaks of invasive group B streptococcal (iGBS; Streptococcus agalactiae ) disease in infants is unknown. We used whole genome sequencing (WGS) of iGBS isolates collected during a period of enhanced surveillance of infant iGBS disease in the UK and Ireland to determine the number of clustered cases. Methods: Potentially linked iGBS cases from infants with early (<7 days of life) or late-onset (7–89 days) disease were identified from WGS data (HiSeq 2500 platform, Illumina) from clinical sterile site isolates collected between 04/2014 and 04/2015. We assessed time and place of cases to determine a single-nucleotide polymorphism (SNP) difference threshold for clustered cases. Case details were augmented through linkage to national hospital admission data and hospital record review by local microbiologists. Results: Analysis of sequences indicated a cutoff of ≤5 SNP differences to define iGBS clusters. Among 410 infant iGBS isolates, we identified 7 clusters (4 genetically identical pairs with 0 SNP differences, 1 pair with 3 SNP differences, 1 cluster of 4 cases with ≤1 SNP differences) of which 4 clusters were uncovered for the first time. The clusters comprised 16 cases, of which 15 were late-onset (of 192 late-onset cases with sequenced isolates) and 1 an early-onset index case. Serial intervals between cases ranged from 0 to 59 (median 12) days. Conclusions: Approximately 1 in 12 late-onset infant iGBS cases were part of a hospital cluster. Over half of the clusters were previously undetected, emphasizing the importance of routine submission of iGBS isolates to reference laboratories for cluster identification and genomic confirmation. Abstract : We used whole genome sequencing data from invasive group B Streptococcus isolates from a 13-month period of national enhanced surveillance in the United Kingdom and Ireland to identify 7 clusters, 4 of which had not been detected when they first occurred.